Reconceptualising the paramountcy: beyond the individualistic construction of the best interests of the child - Moyo, Admark (Juta Law, 2016)
This article laments the individualistic construction of the best interests of the child principle. Decision making in a family context goes beyond a mere trumpeting of the interests of the individual child and involves balancing various competing interests. Decisions often claimed to be made in the interests of children are not just about children - they are an attempt to balance the competing interests of family members. A child's best interests are often limited by the broad interests of the community (especially in communitarian societies) and the rights of others, particularly the rights and interests of parents, siblings, caregivers and other persons exercising parental responsibilities. Consequently, decisions made in a family context usually seek to balance different family members' rights and interests. Drawing inspiration from literature on the subject, the article advocates the adoption of a holistic approach to the welfare principle. It is shown, towards the end of the article, that the South African courts and legislature have rightly endorsed the notion that the fact that the best interests of the child are 'paramount' does not mean that it is not limitable. Much depends on the competing interests at stake, the factors that must be weighed in the process of making a value judgment and the weight to be accorded to each factor in light of the facts of each case.